Streaming culture : subscription platforms and the unending consumption of culture - Arditi, David, 1982- (Emerald Publishing Limited, 2021)
The explosion of services such as Netflix, Spotify, Disney+, Apple Music, Amazon Prime and YouTube, which allow us to access content at the click of a button, has turned the norms surrounding cultural consumption upside down. How has this shift to an apparently unending supply of content affected the way we consume our favourite binge-worthy show, blockbuster movie or hot new album release? Positioning streaming alongside a major shift to contemporary capitalism, David Arditi demonstrates that streaming platforms have created an economy where consumers pay more for the same amount of consumptive time. Encouraging us to look beyond the seemingly limitless supply of multimedia content, Arditi calls attention to the underlying dynamics of instant viewing - in which our access to content depends on any given service's willingness, and ability, to license it.
Includes index.
Keywords: Digital media -- Social aspects.; Multimedia communications -- Social aspects.; Streaming video -- Social aspects.; Acoustic streaming -- Social aspects.; Social Science, Technology Studies.; Media studies.; elektronické knihy; electronic books